Does Riding Behavior Depend on Where You Live? Differences between Regions in Peninsular Malaysia among the Working Population - N.K. Alias; F. Lamin; W.A. Batcha; H. Bakar; R. Ismail (Journal of the Society of Automotive Engineers Malaysia, 2022)
The rising trend of fatal motorcycle accidents in Malaysia is continuously growing since the early 90s. This mode of transportation become popular, particularly in developing and middle-income countries – due to the lower cost of ownership as compared to passenger cars. Through this study, the riding behavior of workers during commuting between different regions in Peninsular Malaysia was compared. Overall, personal safety equipment recorded the highest percentage of non-compliance among the listed behavior in each region. Based on the presented findings, localized riding behavior in the Peninsular Malaysia regional area was determined, i.e., similarity of riding behavior patterns found in central, northern, and southern regions of Peninsular Malaysia. This study is essential as a guide for a strategic regional commuting management plan, especially for those who travel to, from, and for work using a motorcycle.